SP0199 CASE 2 DISCUSSANT: HOW TO TREAT DIFFICULT ILD. (June 2019) - Maher, Toby
Abstract : Background: ILD frequently results in progressive and irreversible destruction of the lung through scarring. Prompt therapy can help rescue lung function and prevent subsequent respiratory decline. This case will demonstrate the challenges inherent in diagnosing and managing interstitial lung disease in the context of connective tissue disease Objectives: To discuss typical presentation of CTD-ILD Review challenge of making diagnosis and choosing best treatment. Assess treatment options, duration of therapy and measurement of treatment response. Conclusion: A range of therapeutic options exist for CTD-ILD albeit with a paucity of trial data to support best practice. Accurate diagnosis of systemic disease, paired with careful assessment and monitoring of the respiratory system are vital in ensuring optimal management. Intravenous therapy is often necessary in advanced disease or for disease which proves refractory to oral immunosuppression. References: [1] Saunders P, Tsipouri V, Keir GJ, Ashby D, Flather MD, Parfrey H, Babalis D, Renzoni EA, Denton CP, Wells AU, Maher TM. Rituximab versus cyclophosphamide for the treatment of connective tissue disease-associated interstitial lung disease (RECITAL): study protocol for a randomised controlled trial. Trials2017; 18: 275. [2] Maher TM. Immunosuppression for connective tissue disease-related pulmonary disease. Seminars in respiratory and critical care medicine2014; 35: 265-273. Disclosure of Interests: Toby Maher Grant/research support from: Received funds from BI advisory board participation and conference travel. Received research funding and/or consulting fees or other remuneration from GSK, UCB, AstraZeneca, Roche, Bayer, Biogen Idec, Cipla, Prometic, and Sanumed. Toby Maher has, via his institution, received industry-academic funding from GlaxoSmithKline R&D and UCB., Consultant for: Toby Maher has received consultancy or speakers fees from Apellis, AstraZeneca, Bayer, Biogen Idec, Boehringer Ingelheim, Galapagos, GlaxoSmithKline R&D, Indalo, Pliant, ProMetic, Roche, Samumed and UCB; and has received consultancy fees from Galecto.